TRACTION RECTIFIER-INVERTER SUBSTATION CONCEPT FOR 3 KV DC RAILWAY TRACTION SYSTEM - Kruczek, Włodzimierz (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2015)
In recent years, all newly manufactured and put into operation electric rail vehicles are equipped with asynchronous motors and have the opportunity to return the energy to the overhead conytact line system during regenerative braking. This energy obtained from the regenerative braking process can be fed back only if on the same OHCL section there is another electric vehicle that is simultaneously generating traction force. In this case this energy can be reused by this second vehicle. In any other case the energy generated by the regenerative braking process is dissipated on braking resistors. Moreover, the energy recuperation and transmission to the local power distribution system could be possible, if the traction substations were equipped with traction rectifier-inverter substation converters instead of traditional rectifiers. Converters are a type of converter semiconductor capable of bi-directional power transmission. This article outlines the technical problems which need to be solved while trying to model, design and to build such an inverter.